Taming Electrons in Pt/C Catalysts to Boost the Mesokinetics of Hydrogen Production. (July 2022) - Chen, Wenyao; Fu, Wenzhao; Duan, Xuezhi; Chen, Bingxu; Qian, Gang; Si, Rui; Zhou, Xinggui; Yuan, Weikang; Chen, De
Abstract: Taming the electron transfer across metal–support interfaces appears to be an attractive yet challenging methodology to boost catalytic properties. Herein, we demonstrate a precise engineering strategy for the carbon surface chemistry of Pt/C catalysts—that is, for the electron-withdrawing/donating oxygen-containing groups on the carbon surface—to fine-tune the electrons of the supported metal nanoparticles. Taking the ammonia borane hydrolysis as an example, a combination of density functional theory (DFT) calculations, advanced characterizations, and kinetics and isotopic analyses reveals quantifiable relationships among the carbon surface chemistry, Pt charge state and binding energy, activation entropy/enthalpy, and resultant catalytic activity. After decoupling the influences of other factors, the Pt charge is unprecedentedly identified as an experimentally measurable descriptor of the Pt active site, contributing to a 15-fold increment in the hydrogen generation rate. Further incorporating the Pt charge with the number of Pt active sites, a mesokinetics model is proposed for the first time that can individually quantify the contributions of the electronic and geometric properties to precisely predict the catalytic performance. Our results demonstrate a potentially groundbreaking methodology to design and manipulate metal–carbon catalysts with desirable properties.